Inefficiencies and opportunities of urban transport in Brazil, a case study of Balneario Camboriú - TISCHER, VINICIUS (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2022)
The objective of this research is to identify the institutional and legal critical factors responsible for the inefficiencies in the urban mobility system in Brazil, to later recommend guidelines on how to overcome counterproductive conditions of the transport system in order to reduce the externalities and improve the quality of life of the population. It was reviewed literature and legislation related to urban mobility applied to Brazilian cities using as a case of study the city of Balneário Camboriú, Brazil. The analysis allowed to understand several factors that can generate negative externalities and reduction on the urban mobility and life quality of the population. As main results, it was identified that the inefficiencies, especially for public transportation, faces several legal and institutional issues, where its truncated policies do not allow that best solutions to be employed.